Concentration Effects on the Spatial Interaction of Corrosion Pits Occurring on Zinc in Dilute Aqueous Sodium Chloride - Natalie Wint (Journal of The Electrochemical Society, 2019)
The scanning vibrating electrode technique is used to study the localized corrosion of unpolarized zinc in near-neutral aqueous sodium chloride electrolyte of varying concentration [NaCl]. As [NaCl] is reduced from 1% (w/v) to 0.0005% (w/v) the morphology of attack changes from large, irregular, areas of anodic zinc dissolution and cathodic oxygen reduction, to a regular array of anodic pits set in an otherwise cathodic surface. In dilute electrolyte ([NaCl] < 0.01%) the total (area averaged) corrosion current density, J, (A·m−2), obtained from a numerical area integral of SVET anodic current density data, is shown to vary with approximately the square root of [NaCl]. The number density of pits, n (m−2) is shown to decrease with increasing [NaCl]. The mean individual pit current, ipit¯¯¯¯, (A = J/n) varies with approximately the square root of [NaCl]. A simple geometric analysis, based on a calculation of the radial dependence of electrical resistance exhibited by a hemispherical shell of electrolyte concentric with the pit, is used to explain the relationship between ohmic potential drop in the external solution, solution conductivity, and the radial distance away from an existing active pit.